Engenharia didática para os estudos de letramento matemático - ARAÚJO, David Geandson da Conceição Bailão (2024)
This article is the result of a qualitative analysis based on a bibliographical review with the initial proposal to understand the structure of didactic engineering and mathematical literacy. The objective is to analyze academic productions that bring the themes of didactic engineering and mathematical literacy aimed at guiding the teaching and learning of school mathematics. The methodology used was bibliographical research, we adopted an approach that involves bibliographical survey, reading of articles, following the dialectical methodological approach. According to Fonseca, bibliographical research is carried out. “[...] based on the survey of theoretical references already analyzed, and published by written and electronic means, such as books, scientific articles, website pages (2002, p. 32).” The results show that together, these works provide a comprehensive view, from theoretical construction to practical application, highlighting the relevance of didactic engineering in the context of mathematical literacy. This in-depth analysis serves as a starting point for future research and educational practices aimed at to enrich teaching and learning. We conclude that the identification of the main elements present in these works provided a deeper understanding of the approaches and proposals for mathematical literacy from the perspective of didactic engineering. The in-depth understanding of the relationship between mathematical literacy and didactic engineering enables teachers to integrate different pedagogical theories, such as the Anthropological Theory of Didactics (TAD), thus enriching their educational practices.